Nutrition education through provision of additional local food for pregnant women and toddlers in Kalisat District, Jember Regency - Erlyna Jayeng Wijayanti; Juliana Christyaningsih; Umul Annisa Fadhila; Ainur Rifda Kurnia Puspita Sari (Community Empowerment, 2022)
The Nahdlatul Ulama Health Institute (LKNU), Puskesmas in the Jember Region and Poltekkes Kemenkes Surabaya held community service activities aimed at reducing the prevalence of stunting under five. The activity began with family assistance for pregnant women and stunting toddlers, which were attended by 112 mothers of toddlers and 40 pregnant women, and continued with nutrition education conducted by nutrition counseling with media in the form of posters, flipcharts and games. The third is the provision of nutritional intake for pregnant women and toddlers through Supplementary Food Provision (PMT), and the last is demonstration of examples of balanced nutrition for toddlers according to the principle of balanced nutrition through the use of local food ingredients. The results of the activity revealed an increase in the knowledge of pregnant women and mothers of toddlers by 47%, an increase in the attitudes of pregnant women by 4% and mothers of toddlers by 1.9%, as well as an increase in the practice behavior of pregnant women and mothers of toddlers in preparing and providing a balanced nutritional menu of local food.